Unveiling The Potential of Jimbu (Allium przewalskianum): Bioactive Compounds, Antioxidant, and Antimicrobial Properties of a Native Himalayan Spice Herb - Pandey, Shreejana; Chataut, Guheswari; Maharjan, Suja; Maidali, Dev Raj; Bhattarai, Keshab (International Journal of Applied Sciences and Biotechnology, 2023)
Jimbu (Allium przewalskianum), is an indigenous Himalayan spice herb in Nepal and has a long history of culinary use, yet its potential beyond home kitchens remains largely unexplored due to limited studies and exposure. It does not require extensive input of cash, machinery, land, or labor to profit from, making it an excellent and valuable source of pharmaceutical ingredients owing to its bioactive compounds. We investigated its antioxidant and antimicrobial properties. Quantitative analysis of Jimbu extracts revealed the presence of bioactive compounds, including Oleoresin (extracted using acetone and methanol), polyphenols, flavonoids, and tannins. The methanol extract of. A. przewalskianum exhibited the highest polyphenol content (8.11±0.24 mg GAE/g), flavonoid content (5.28±0.29 mg GAE/g) and tannin content (0.923±0.02 mg GAE/g). The antioxidant potential of Jimbu was seen to be increased with an increase in concentration, reaching 58.79% at 400µg/ml, with an IC50 value of 303.58µg/ml for DPPH radical scavenging activity. Likewise, the yield of oleoresin was obtained as (10.86±0.27) from acetone and (7.8±0.20) from methanol. Similarly, sensory evaluation through One-way ANOVA highlighted concentrations of 0.07% and 0.1% of Oleoresin to be most favored. Furthermore, sensory evaluation of the Jimbu extracts in minced chicken meat exhibited remarkable antimicrobial activity against Salmonella along with a significant reduction in the colony forming units (CFU). This study shows that the extracts of A. przewalskianum could be utilized as a potential medicinal plant for the development of effective drugs against pathogenic bacteria. Meanwhile, it provides opportunities for economic benefits and a new potential revenue source for rural communities in the Himalayan region of Nepal. Int. J. Appl. Sci. Biotechnol. Vol 11(4): 171-180.